Determinants of Firm-Level Voluntary Corporate Disclosure in Emerging Markets: A Meta-Regression Analysis - P. Bishagazi, Kaihula (Journal of Public Administration and Governance, 2023)
The purpose of this paper is to determine which factors are most important in voluntary corporate disclosure at firm level in emerging markets. The study characteristics that cause differences in results in the original empirical studies are also examined. This study applies a meta- regression technique developed by Stanley and Jarrell (1989) to a sample of 32 empirical studies published between 2011 and 2020. The study findings reveal that the financial crisis variable, region of the study variable, and weighting of the dependent variable significantly affect study results of the original empirical researches. Moreover, the most important and robust determinants of corporate disclosure in emerging markets are board independence and foreign listing status. Study findings also indicate that firm size, which is identified by most empirical studies to be a significant and most robust determinant of corporate disclosure, to be insignificant in this meta-regression study. This study will help to resolve the ambiguity that has existed over the past decade in literature as to which factors are really important in voluntary corporate disclosure practices in emerging countries. Secondly, this study extends the literature relating to corporate disclosure practice in emerging countries.